Genomics of Rare Hematologic Cancers - Solé, Francesc (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The primary aim of this reprint is to describe the genomics of splenic lymphomas, hairy cell leukemia, Cutaneous lymphomas, plasma cell leukemia, MDS with deletion 5q, mastocytosis, hypodiploid acute lymphoblastic leukemia, CLL with complex karyotype and other rare hematologic cancers.